Central banking - Kock, M.H.de (Delhi Granada Publishing Ltd, 1995)
The book deals first with the evolution of central banking and the establishment of central banks in almost every independent country in the world, and then gives detailed outline of all the important functions and operations of the central bank.
Includes index
osc 15/8/17
Loans
Keywords: Central Banking; Banks and banking